Development and Validation of a Bilingual Stroke Preparedness Assessment Instrument. Issue 4 (April 2017) - Skolarus, Lesli E.; Mazor, Kathleen M.; Sánchez, Brisa N.; Dome, Mackenzie; Biller, José; Morgenstern, Lewis B.
Abstract : Background and Purpose—: Stroke preparedness interventions are limited by the lack of psychometrically sound intermediate end points. We sought to develop and assess the reliability and validity of the video-Stroke Action Test (video-STAT) an English and a Spanish video-based test to assess people's ability to recognize and react to stroke signs. Methods—: Video-STAT development and testing was divided into 4 phases: (1) video development and community-generated response options, (2) pilot testing in community health centers, (3) administration in a national sample, bilingual sample, and neurologist sample, and (4) administration before and after a stroke preparedness intervention. Results—: The final version of the video-STAT included 8 videos: 4 acute stroke/emergency, 2 prior stroke/nonemergency, 1 nonstroke/emergency, and 1 nonstroke/nonemergency. Acute stroke recognition and action response were queried after each vignette. Video-STAT scoring was based on the acute stroke vignettes only (score range 0–12 best). The national sample consisted of 598 participants, 438 who took the video-STAT in English and 160 who took the video-STAT in Spanish. There was adequate internal consistency (Cronbach α=0.72). The average video-STAT score was 5.6 (SD=3.6), whereas the average neurologist score was 11.4 (SD=1.3). There was no difference in video-STAT scores between the 116 bilingual video-STAT participants who took the video-STAT in English or Spanish. Compared with baseline scores, the video-STAT scores increased after a stroke preparedness intervention (6.2 versus 8.9, P <0.01) among a sample of 101 black adults and youth. Conclusions—: The video-STAT yields reliable scores that seem to be valid measures of stroke preparedness. Abstract : Supplemental Digital Content is available in the text.